Pycnodysostosis: a distinctive brittle bone disease? - K., Muralidhara; Padanad, Gouramma; Kumar, T. S. Srinath (International Journal of Research in Medical Sciences, 2016)
Pycnodysostosis is a rare disorder that is inherited as an autosomal recessive trait usually diagnosed at an early age with an estimated incidence of 1.7 per 1 million births. It is a rare clinical entity, first described in 1962 by Maroteaux and Lamy. The disease has also been named Toulouse-Lautrec syndrome, after the French artist Henri de Toulouse-Lautrec, who suffered from the disease. Pycnodysostosis is a lysosomal storage disorder of the bone caused by a mutation in the gene that codes the enzyme Cathepsin K causing osteosclerosis. However, the diagnosis is sometimes late, made as a result of bone fracture, given the severe bone fragility resulting from increased bone density. Oral and maxillofacial manifestations of this disease are very common.